The Influence of Learning Readiness, Learning Discipline, Gadget Use, Learning Facilities, and Family Socioeconomic Conditions on the Learning Achievement of 11th Grade Students in Economics Subjects - Fajar Al-Ghivari; Stevani; Yosi Eka Putri (Global Action and Education for Society, 2026)
This study aims to analyze the influence of Learning Readiness, Learning Discipline, Gadget Usage, Learning Facilities, and Family Socio-Economic Conditions on the Academic Achievement of Eleventh-Grade Students in the Economics Subject at MAN 1 Pasaman Barat. This research employed a quantitative method with an associative approach. The population consisted of all eleventh-grade students at MAN 1 Pasaman Barat totaling 195 students. A sample of 94 students was selected using the stratified random sampling technique. The research instruments consisted of a Likert-scale questionnaire tested for validity and reliability, as well as documentation of students’ Economics report card scores. Data were analyzed using multiple linear regression analysis. The t-test was used to examine the partial effects, the F-test to examine simultaneous effects, and the coefficient of determination (R²) to measure the contribution of the independent variables to the dependent variable. The results indicated that, partially, learning readiness, learning discipline, gadget usage, learning facilities, and family socio-economic conditions had a significant effect on students’ academic achievement. Simultaneously, these five independent variables also had a significant effect on the academic achievement of eleventh-grade students in the Economics subject at MAN 1 Pasaman Barat.